Египетские поселенцы в Вавилонии в VI-V вв. до н. э. - Дандамаев, M. A. (1967)
Dandamajev, M. A.; Ägyptische Deportierte im Babylonien des VI. und V. Jahrhunderts v. Chr.; GCCI I 327; Strassmaier, Camb. 85; UMBS II 91; BE X 23; Strassmaier, Camb. 334; YBT VI 148.